Grid section for roasting trolley and preparation method thereof
By using chromium-nickel alloy substrate and composite coating technology on the trolley grate bar of the belt calcining unit, the problem of rapid failure of the grate bar under high temperature and flue gas erosion is solved, and a longer service life and better wear resistance and oxidation resistance are achieved.
Patent Information
- Application Number
- CN202411927087.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the existing steel smelting pellet sintering process, the trolley grate strip of the belt roasting unit is susceptible to high temperature, flue gas erosion and material ball unloading wear, resulting in rapid failure.
A chromium-nickel alloy substrate is used, and a CoNiCrAlY base layer and a CoCrAlYTa base layer are deposited on its surface. The sealing treatment is combined with a low viscosity sealing resin to form a composite coating to improve wear resistance, oxidation and erosion resistance.
It significantly extends the service life of the grate, improves high-temperature wear resistance, impurity adhesion, high-temperature oxidation and corrosion resistance, and reduces wear and failure efficiency.
Smart Images

Figure HDA0005209490610000011 
Figure HDA0005209490610000012 
Figure HDA0005209490610000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of smelting pellet sintering, and particularly relates to a grate bar for a steel belt roasting unit trolley and a preparation method thereof. Background Art
[0002] In the steel smelting pellet sintering process, the belt roaster mainly works in the roasting equipment, which includes drying, preheating, roasting, equalizing and cooling areas. The processing temperature of each section is gradually heated from room temperature to about 1300℃. The processing heat is input to the corresponding drying, preheating and roasting through the waste heat hot air system of different cooling sections. The highest temperature of the hot air is about 1250℃. The hot air passes through the gaps between the grate bars from the bottom to the top of the trolley to heat the pellet materials carried on the grate bars of the trolley. The belt roasting trolley operation system is a step-by-step reciprocating structure. The operating power is provided by the main shaft gear chain. The pellets and grate bars move at a uniform speed with the trolley in the roasting equipment. The belt roasting unit has about 160 trolleys, and each trolley is equipped with about 320 grates.
[0003] The grate bars of the trolley are key equipment for carrying pellet materials. They are vulnerable parts among the trolley components and are the key factors leading to the failure of the trolley. The main failure forms of the grate bars are the wear and tear of the ball unloading and the erosion of the flue gas containing metal particles, which leads to the increase of the gap between the adjacent grate bars, resulting in the leakage of the ball from the gap. Among them, the erosion effect of the flue gas containing metal particles is relatively small, which is mainly caused by the sliding erosion and wear of the ball when unloading. Usually, the grate bars of the trolley used in the pellet belt roasting machine are made of high-alloy cast steel, but due to the high working environment temperature, periodic rapid temperature rise and drop, and a large temperature range, repeated high-temperature erosion of hot air flue gas, and dust of different particle sizes in the flue gas, the grate bars are prone to oxidation reactions during service, resulting in problems such as loose surface structure. In addition, after the roasting process is completed, the trolley unloads by tilting the car body. The strength and hardness of the finished ball after processing are relatively high, and the impact and sliding wear on the upper edge of the grate bar are relatively large, which is easy to gradually wear and fail during the reciprocating process and unloading process. Summary of the invention
[0004] The main purpose of the present invention is to address the problems and shortcomings of the prior art and provide a grate bar for a pellet belt roasting trolley. The grate bar adopts a chromium-nickel alloy substrate and is combined with a thermal spray composite coating. The grate bar has good high-temperature wear resistance, resistance to impurity adhesion, high-temperature oxidation resistance and erosion resistance, and can effectively extend the service life in the belt roasting trolley operation system.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A grate bar for a baking trolley comprises a chromium-nickel alloy substrate and a thermally sprayed composite coating deposited on the surface thereof after a sealing treatment; the thermally sprayed composite coating comprises a CoNiCrAlY base layer and a CoCrAlYTa-based high-temperature resistant gradient surface layer, wherein the CoCrAlYTa-based high-temperature resistant gradient surface layer comprises CoCrAlYTa and a heat-resistant oxide, and the content of the heat-resistant oxide is distributed in a gradient from the surface to the inside of the coating.
[0007] Furthermore, in the CoCrAlYTa-based high-temperature resistant gradient surface layer, the heat-resistant oxide content is distributed in a gradient decreasing manner from the surface to the inside along the coating thickness direction.
[0008] Furthermore, in the CoCrAlYTa-based high temperature resistant gradient surface layer, the content of heat resistant oxide is 5-15wt%.
[0009] In the above scheme, the stoichiometric formula of CoCrAlYTa is shown in Formula I;
[0010] Co a Cr b Al c Y d Ta e (I);
[0011] Wherein, in terms of atomic percentage, 50%≤a≤65%, 15%≤b≤25%, 8%≤c≤12%, 0.3%≤d≤0.8%, and 0.5%≤e≤5%.
[0012] In the above scheme, the heat-resistant oxide can be selected from one or more of aluminum oxide (Al2O3), chromium oxide (Cr2O3), zirconium oxide (ZrO2), yttrium oxide (Y2O3), lanthanum oxide (La2O3) and the like.
[0013] Furthermore, the CoCrAlYTa-based high temperature resistant gradient surface layer is obtained by plasma spraying using CoCrAlYTa powder (stoichiometric formula see formula I) and heat resistant oxide powder as main raw materials using a double powder feeding process.
[0014] Furthermore, the CoCrAlYTa powder is prepared by a vertical powder feeding process, and the heat-resistant oxide powder is prepared by an oblique powder feeding process.
[0015] Furthermore, the particle size of the CoCrAlYTa raw material powder is 15 to 45 μm, and the particle size of the heat-resistant oxide powder is 30 to 55 μm.
[0016] Furthermore, the heat-resistant oxide powder is Al2O3 powder, which has high hardness and excellent oxidation resistance, and can significantly improve the corrosion resistance and wear resistance of the coating.
[0017] Furthermore, the CoCrAlYTa base layer gradient coating mainly controls the Al2O3 content of different thicknesses to 3% to 20% by adjusting the Al2O3 oblique powder feeding amount, thereby preparing a coating structure with a gradient change in Al2O3 content.
[0018] In the above scheme, the stoichiometric formula of the main components of the CoNiCrAlY substrate layer is shown in Formula II;
[0019] Co a Ni b Cr c Al d Y e (II)
[0020] Wherein, in terms of atomic percentage, 40%≤a≤60%, 20%≤b≤40%, 10%≤c≤20%, 5%≤d≤15%, and 0.1%≤e≤1%.
[0021] In the above scheme, the CoNiCrAlY substrate layer is obtained by supersonic flame spraying using CoNiCrAlY powder (stoichiometric formula shown in Formula II) as the main raw material.
[0022] Furthermore, the CoNiCrAlY powder is a spherical CoNiCrAlY powder that is atomized and granulated.
[0023] Furthermore, the CoNiCrAlY powder is a spherical powder of 15 to 45 μm and has a bulk density of 4.5 to 5.0 g / m 3 , good fluidity, which is beneficial to improve the heating uniformity during the spraying process, and is not prone to overoxidation, thereby forming a uniform and dense coating.
[0024] In the above scheme, the stoichiometric formula of the main component of the chromium-nickel alloy substrate is as shown in formula (III),
[0025] Fe a C b Si c Mn d Cr e Ni f M g (III);
[0026] Wherein, M is a trace element and an unavoidable impurity element, and in terms of atomic percentage, 54%≤a≤65%, 0.2%≤b≤0.5%, 0%≤c≤2%, d≤2%, 24%≤e≤28%, and 11%≤f≤14%.
[0027] In the above scheme, matching notches for mechanically and physically connecting to the trolley frame are provided at both ends of the grates for the roasting trolley.
[0028] Furthermore, the inner side of the matching notch has an inclined structure that matches the slot of the trolley frame.
[0029] In the above scheme, both sides of the grate bars of the roasting trolley are provided with convex structures for isolating the grate bars from other adjacent grate bars, so that gaps are left between adjacent grate bars for hot air to pass through.
[0030] Furthermore, the convex structure has two sides with triangular structures that are larger at the bottom and smaller at the top, which are used to prevent the pellets from gathering in the gaps between adjacent grate bars during the stacking process, and the middle is an equilateral rhombus, an unequal-sided rhombus or a triangular structure.
[0031] In the above scheme, the sealing treatment is to use a sealing agent to compensate for the microporous characteristics of the thermal spray coating.
[0032] Furthermore, the microporous characteristic refers to the fact that during the use of the thermal sprayed workpiece, the high-temperature gas carries some impurity elements and penetrates into the coating through the micropores, reacts with the substrate to cause expansion, destroys the coating structure, and produces pitting, corrosion pits and other phenomena, resulting in coating failure.
[0033] Furthermore, the sealing agent used in the sealing treatment is a low-viscosity liquid resin; the components and their mass percentages include: 30% to 50% sodium silicate, 10% to 25% polyester resin, 10% to 30% quartz powder, 2% to 10% curing agent, 0.5% to 3% sodium hydroxide, and 5% to 15% calcium carbonate. The sealing agent used in the present invention has a maximum heat-resistant temperature of up to 1500°C. Under high temperature conditions, the organic matter inside the sealing agent begins to transform into inorganic matter, filling the micropores of the coating and providing a certain strength support for the coating.
[0034] In the above scheme, the preparation step of the sealing agent includes: stirring and mixing the raw materials weighed according to the ratio; and the curing conditions after coating are: heating to 200-250° C. for rapid curing (2-3 hours).
[0035] Furthermore, the sealant can be mixed with various pigments and fillers and applied to substrates by various construction methods such as spreading, dipping, spraying, brushing, and roller coating. The substrates include but are not limited to metals, alloys, glass, ceramics, paint films, fiberglass, and polymer materials.
[0036] The present invention also provides a method for preparing the above-mentioned grate bars for the roasting trolley, comprising the following steps:
[0037] 1) According to the designed structural characteristics, the chromium-nickel alloy is formed into grate bars by static precision casting, and the cast grate bars are cleaned and roughened;
[0038] 2) preparing a CoNiCrAlY substrate layer on the surface of the workpiece obtained in step 1) by using a supersonic flame spraying process;
[0039] 3) using a plasma thermal spraying process to prepare a CoCrAlYTa-based high temperature resistant gradient surface layer on the surface of the workpiece obtained in step 2);
[0040] 4) A sealing agent is coated on the surface of the workpiece obtained in step 3), and the workpiece is heated and rapidly cured to obtain the grate bars for the baking trolley.
[0041] In the above scheme, the cleaning step in step 1) uses an organic solvent, and the specific cleaning agent that can be selected is acetone, isopropanol, ethyl acetate or citric acid.
[0042] In the above scheme, in step 1), the workpiece surface is roughened to a roughness of Ra 4-6 and the sprayed surface is non-reflective; its main purpose is to increase the adhesion of the workpiece surface and lay a good foundation for the subsequent thermal spraying process.
[0043] In the above scheme, in step 2), the workpiece needs to be fixed in a clamping chuck when the workpiece is sprayed, and the clamping part of the workpiece is protected by high-temperature tape and copper pads.
[0044] Furthermore, during the spraying of step 2), the workpiece is equally divided into left and right parts, and the spraying is performed in different areas. The workpiece rotates at a constant speed during the spraying process, and the spray gun is controlled by an ABB robot arm.
[0045] Furthermore, the composite coating base layer is treated by supersonic flame spraying process, and the adopted process parameters include: spraying distance 300-400mm, oxygen flow rate 1800-2000scfh, fuel flow rate 4.5-5.5gph, auxiliary gas flow rate 23-27scfh, and powder feeding speed 40-50g / min.
[0046] Furthermore, in the supersonic flame spraying process, a powder raw material (CoNiCrAlY) prepared by an atomization granulation process is used. The raw material prepared by this process has high purity, uniform particle size, good fluidity, and is more conducive to forming a uniform coating.
[0047] Furthermore, the CoNiCrAlY base layer has a thickness of 20 to 35 μm.
[0048] In the above scheme, the CoCrAlYTa-based high temperature resistant gradient surface layer is processed by a plasma thermal spraying process, wherein CoCrAlYTa is the coating matrix and contains a gradient distributed heat resistant oxide.
[0049] Furthermore, in the CoCrAlYTa-based high-temperature resistant gradient surface layer, the content of the heat-resistant oxide in the upper surface layer is 13-20wt%, and the content of the heat-resistant oxide in the lower surface layer is 3-5.5wt%.
[0050] The coating adopts a double powder feeding process. During the spraying process, the gradient distribution of the heat-resistant oxide in the coating is controlled by adjusting the powder feeding rates of the heat-resistant oxide powder and the CoCrAlYTa powder.
[0051] Furthermore, the plasma thermal spraying process parameters include: spray gun distance 100-300 mm, argon flow rate 45-65 NLPM, hydrogen flow rate 9-15 NLPM, current 520-580 A, powder feeding speed 25.5-28.5 g / min (CoCrAlYTa), 1.45-4.5 g / min (heat-resistant oxide powder).
[0052] Furthermore, during the spraying process, the average thickness of each sprayed coating is 8 to 18 μm, and the amount of heat-resistant oxide in the powder feeding raw material is increased proportionally after every 2 to 10 sprayings.
[0053] Furthermore, after every 2 to 10 sprayings, the amount of the heat-resistant oxide powder is adjusted by increasing the heat-resistant oxide powder by 4 to 6% (absolute value, absolute value of the percentage of the heat-resistant oxide powder in the mixed powder).
[0054] Furthermore, the CoCrAlYTa base layer has a thickness of 100 to 250 μm.
[0055] In the above scheme, in order to prevent the workpiece from being deformed due to overheating, spraying needs to be stopped after each spraying, and a high-pressure air gun is used to cool the workpiece. Spraying can be carried out again after the temperature drops below 50°C. After the spraying operation is completed, it is placed in an open environment to cool naturally.
[0056] In the above scheme, the coating formed by plasma thermal spraying has microporous characteristics. During the use of the workpiece, the high-temperature gas will carry some impurity elements into the coating through the micropores, react with the substrate to cause expansion, destroy the coating structure, and produce pitting, corrosion pits and other phenomena, which eventually lead to coating failure and require sealing treatment of the coating; the sealing agent used in the present invention is a low-viscosity liquid resin specially designed for thermal spraying systems, which can be quickly cured between 200 and 250°C, and can be applied to various types of substrates by various construction methods such as smearing, immersion, brushing, roller coating, etc., and can remain stable below 1500°C.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] 1) High temperature wear resistance; the grate bars obtained by the present invention still maintain a low wear amount after reciprocating heating and cooling wear during service;
[0059] 2) Resistance to impurity adhesion Minerals will melt at high temperatures and easily produce some solid solutions, which will chemically react with the matrix and adhere to the surface of the workpiece. The CoNiCrAlY base layer introduced in the present invention has a thermal expansion coefficient similar to that of the workpiece matrix material. On the one hand, it can alleviate the internal tension between the matrix and the gradient coating due to the different thermal expansion coefficients. On the other hand, it has good bonding strength with the matrix and the gradient coating, ensuring good overall performance and preventing peeling during use.
[0060] 3) Resistance to high temperature oxidation; Heat-resistant oxides such as CoCrAlYTa and Al2O3 have good resistance to high temperature oxidation and thermal shock, but their thermal expansion coefficients are quite different from those of the substrate. The present invention further adopts a gradient heat-resistant oxide content coating construction form, using the heat-resistant oxide as a gradient phase, and slowing down the internal tension generated when the heat-resistant oxide phase shrinks by stacking layers, thereby reducing the influence of the high thermal expansion coefficient on the coating. In addition, a CoNiCrAlY layer is provided between the gradient coating and the substrate to further slow down the influence of its internal tension and further improve the overall performance.
[0061] 4) Good physical properties: The surface layer of the coated grate bars of the present invention is a gradient coating composed of CoCrAlYTa and a heat-resistant oxide phase. CoCrAlYTa has good resistance to high-temperature gas erosion and corrosion, while the reinforcing phase heat-resistant oxide has a high melting point and has strong resistance to chemical corrosion. In the gradient ceramic-based coating, the closer to the outer surface, the higher the content of the heat-resistant oxide phase. The high content of the heat-resistant oxide phase can effectively prevent problems such as high-temperature oxidation and corrosion by chemical gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 A front view of a grate bar structure according to an embodiment of the present invention;
[0063] Figure 2 A top view of a grate bar structure according to an embodiment of the present invention;
[0064] Figure 3 A side view of a grate bar structure according to an embodiment of the present invention;
[0065] Figure 4 A three-dimensional view of a grate bar structure according to an embodiment of the present invention;
[0066] In the figure, 1 is a notch and 2 is a convex structure;
[0067] Figure 5 The figure shows the morphology of the worn surface of the sample before and after the grate wear test described in an embodiment, wherein the left figure shows before wear and the right figure shows after wear. DETAILED DESCRIPTION
[0068] In order to more clearly and thoroughly illustrate the advantages of the present invention, the present invention is further described in detail through the following specific implementation cases and accompanying drawings. The specific embodiments described herein are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. After reading the present invention, the various equivalent forms of modifications to the present invention by those skilled in the art are all within the scope of the claims attached to this application.
[0069] In the following embodiments, the chromium-nickel alloy substrate and the CoNiCrAlY base layer, CoCrAlYTa base surface layer and sealing layer deposited on the surface are used. The structural schematic diagram is shown in FIG. Figure 1-4 .
[0070] Example 1
[0071] A grate bar for a roasting trolley, the preparation method of which comprises the following steps:
[0072] 1) Use chromium-nickel alloy static precision casting to form the grate bar base material (see the structural diagram Figure 1-4 ), the main chemical components used are based on the formula Fe a C b Si c Mn d Cr e Ni f M g The ingredients are prepared, wherein a, b, c, d, e, f, and g represent the atomic percentages of the corresponding components: a 58%, b 0.35%, c 1%, d 0.5%, e 26%, f 13.5%, and g 0.65%;
[0073] 2) The workpiece surface obtained in step 1) is cleaned with acetone, and then the workpiece surface is roughened with 46# white corundum (operated with a handheld air gun) until the workpiece surface roughness is Ra 4-6 and the sprayed surface is non-reflective;
[0074] 3) A CoNiCrAlY substrate layer is prepared on the surface of the workpiece obtained in step 2) by using a supersonic flame spraying process, and the main chemical components are selected according to the formula Co a Ni b Cr c Al d Y e The ingredients are prepared, wherein a is 52%, b is 25.5%, c is 12%, d is 10%, and e is 0.5%, and the average thickness of the prepared base layer is about 20 μm; the adopted supersonic flame spraying process parameters include spraying distance 350 mm, oxygen flow rate 1900 scfh, fuel flow rate 5.0 gph, auxiliary gas flow rate 25 scfh, and powder feeding speed 44 g / min;
[0075] 4) Use the main chemical components according to the formula Co a Cr b Al c Y d Ta e The ingredients are prepared as follows: a 62%, b 23%, c 11%, d 0.5%, and e 3.5%. CoCrAlYTa powder and heat-resistant oxide powder Al2O3 are used as the main raw materials, and a CoCrAlYTa-based high-temperature resistant gradient surface layer is prepared by plasma spraying using a double powder feeding process, and its average thickness is about 180 μm; wherein the plasma spraying process parameters used include: a spray gun distance of 200 mm, an argon flow rate of 52 NLPM, a hydrogen flow rate of 13 NLPM, and a current of 550 A; the first layer (first pass) of the gradient coating, i.e., the 5wt% Al2O3 layer, adopts a powder feeding rate of 1.45-1.8 g / min (Al2O3), 27.5-28.5 g / min (CoCr The second layer of the gradient coating, i.e., the 10wt% Al2O3 layer, was sprayed 6 times at a powder feeding rate of 2.5-2.9g / min (Al2O3) and 22.5-26.5g / min (CoCrAlYTa), with an average coating thickness of 15μm per layer; the third layer of the gradient coating, i.e., the 15wt% Al2O3 layer, was sprayed 4 times at a powder feeding rate of 3.5-4.5g / min (Al2O3) and 19.8-25.5g / min (CoCrAlYTa), with an average coating thickness of 15μm per layer;
[0076] 5) The surface of the workpiece obtained in step 4) is sealed with a low-viscosity sealing resin, wherein the raw materials used in the low-viscosity sealing resin and their weight proportions are: 40% sodium silicate, 18% maleic anhydride polyester resin, 20% quartz powder, 5% bishydroxyphthalimide epoxy resin curing agent, 2% sodium hydroxide, and 15% calcium carbonate. The weighed raw materials are mixed evenly, then coated on the surface of the obtained CoCrAlYTa-based high-temperature resistant gradient surface layer, and heated to 230°C for rapid curing to obtain the grate bars for the baking trolley.
[0077] Example 2
[0078] A grate bar for a roasting trolley, the preparation method of which comprises the following steps:
[0079] 1) Use chromium-nickel alloy static precision casting to form the grate bar base material (see the structural diagram Figure 1-4 ), the main chemical components used are based on the formula Fe a C b Si c Mn d Cr e Ni f Mg The ingredients are prepared, wherein a, b, c, d, e, f, and g represent the atomic percentages of the corresponding components: a 58%, b 0.35%, c 1%, d 0.5%, e 26%, f 13.5%, and g 0.65%;
[0080] 2) The workpiece surface obtained in step 1) is cleaned with acetone, and then the workpiece surface is roughened with 46# white corundum (operated with a handheld air gun) until the workpiece surface roughness is Ra 4-6 and the sprayed surface is non-reflective;
[0081] 3) A CoNiCrAlY substrate layer is prepared on the surface of the workpiece obtained in step 2) by using a supersonic flame spraying process, and the main chemical components are selected according to the formula Co a Ni b Cr c Al d Y e The ingredients are prepared, wherein a is 52%, b is 25.5%, c is 12%, d is 10%, and e is 0.5%, and the average thickness of the prepared base layer is about 30 μm; the adopted supersonic flame spraying process parameters include spraying distance 350 mm, oxygen flow rate 1900 scfh, fuel flow rate 5.0 gph, auxiliary gas flow rate 25 scfh, and powder feeding speed 46 g / min;
[0082] 4) Use the main chemical components according to the formula Co a Cr b Al c Y d Ta eThe ingredients are a 62%, b 23%, c 11%, d 0.5%, and e 3.5%. CoCrAlYTa powder and heat-resistant oxide powder Al2O3 are used as the main raw materials, and a CoCrAlYTa-based high-temperature resistant gradient surface layer is prepared by plasma spraying using a double powder feeding process, and its average thickness is about 170μm; wherein the plasma spraying process parameters used include: a spray gun distance of 200mm, argon flow rate of 52NLPM, hydrogen flow rate of 13NLPM, and current of 550A; the first layer (first pass) of the gradient coating, i.e., the 5wt% Al2O3 layer, adopts a powder feeding rate of 1.45-1.8g / min (Al2O3), 27.5-28.5g / min (CoCr The second layer of the gradient coating, i.e., the 10wt% Al2O3 layer, was sprayed 8 times at a powder feeding rate of 2.5-2.9g / min (Al2O3) and 22.5-26.5g / min (CoCrAlYTa), with an average coating thickness of 10μm per layer; the third layer of the gradient coating, i.e., the 15wt% Al2O3 layer, was sprayed 4 times at a powder feeding rate of 3.5-4.5g / min (Al2O3) and 19.8-25.5g / min (CoCrAlYTa), with an average coating thickness of 15μm per layer;
[0083] 5) The surface of the workpiece obtained in step 4) is sealed with a low-viscosity sealing resin, wherein the raw materials used in the low-viscosity sealing resin and their weight proportions are: 40% sodium silicate, 18% maleic anhydride polyester resin, 20% quartz powder, 5% bishydroxyphthalimide epoxy resin curing agent, 2% sodium hydroxide, and 15% calcium carbonate. The weighed raw materials are mixed evenly, then coated on the surface of the obtained CoCrAlYTa-based high-temperature resistant gradient surface layer, and heated to 230°C for rapid curing to obtain the grate bars for the baking trolley.
[0084] Example 3
[0085] A grate bar for a roasting trolley, the preparation method of which comprises the following steps:
[0086] 1) Use chromium-nickel alloy static precision casting to form the grate bar base material (see the structural diagram Figure 1-4 ), the main chemical components used are based on the formula Fe a C b Si c Mn d Cr e Ni f M gThe ingredients are prepared, wherein a, b, c, d, e, f, and g represent the atomic percentages of the corresponding components: a 58%, b 0.35%, c 1%, d 0.5%, e 26%, f 13.5%, and g 0.65%;
[0087] 2) The workpiece surface obtained in step 1) is cleaned with acetone, and then the workpiece surface is roughened with 46# white corundum (operated with a handheld air gun) until the workpiece surface roughness is Ra 4-6 and the sprayed surface is non-reflective;
[0088] 3) A CoNiCrAlY substrate layer is prepared on the surface of the workpiece obtained in step 2) by using a supersonic flame spraying process, and the main chemical components are selected according to the formula Co a Ni b Cr c Al d Y e The ingredients are prepared, wherein a is 52%, b is 25.5%, c is 12%, d is 10%, and e is 0.5%, and the average thickness of the prepared base layer is about 35 μm; the adopted supersonic flame spraying process parameters include spraying distance 350 mm, oxygen flow rate 1900 scfh, fuel flow rate 5.0 gph, auxiliary gas flow rate 25 scfh, and powder feeding speed 47 g / min;
[0089] 4) Use the main chemical components according to the formula Co a Cr b Al c Y d Ta eThe ingredients are prepared as follows: a 62%, b 23%, c 11%, d 0.5%, and e 3.5%. CoCrAlYTa powder and heat-resistant oxide powder Al2O3 are used as the main raw materials, and a CoCrAlYTa-based high-temperature resistant gradient surface layer is prepared by plasma spraying using a double powder feeding process, and the average thickness is about 165 μm. Among them, the plasma spraying process parameters used include: a spray gun distance of 200 mm, an argon flow rate of 52 NLPM, a hydrogen flow rate of 13 NLPM, and a current of 550 A; the first layer of the gradient coating, i.e., a 5wt% Al2O3 layer, adopts a powder feeding rate of 1.45-1.8 g / min (Al2O3), 27.5-28.5 g / min (CoCrAlY Ta) was sprayed for 3 times, and the average thickness of each spray coating was 10μm; the second layer of the gradient coating, i.e., the 10wt% Al2O3 layer, was sprayed for 6 times at a powder feeding rate of 2.5-2.9g / min (Al2O3) and 22.5-26.5g / min (CoCrAlYTa), and the average thickness of each spray coating was 15μm; the third layer of the gradient coating, i.e., the 15wt% Al2O3 layer, was sprayed for 3 times at a powder feeding rate of 3.5-4.5g / min (Al2O3) and 19.8-25.5g / min (CoCrAlYTa), and the average thickness of each spray coating was 15μm;
[0090] 5) The surface of the workpiece obtained in step 4) is sealed with a low-viscosity sealing resin, wherein the raw materials used in the low-viscosity sealing resin and their weight proportions are: 40% sodium silicate, 18% maleic anhydride polyester resin, 20% quartz powder, 5% bishydroxyphthalimide epoxy resin curing agent, 2% sodium hydroxide, and 15% calcium carbonate. The weighed raw materials are mixed evenly, then coated on the surface of the obtained CoCrAlYTa-based high-temperature resistant gradient surface layer, and heated to 230°C for rapid curing to obtain the grate bars for the baking trolley.
[0091] Comparative Example 1
[0092] A grate bar for a roasting trolley, the preparation method of which comprises the following steps:
[0093] 1) Use chromium-nickel alloy static precision casting to form the grate bar base material (see the structural diagram Figure 1-4 ), the main chemical components used are based on the formula Fe a C b Si c Mn d Cr e Ni f M g The ingredients are prepared, wherein a, b, c, d, e, f, and g represent the atomic percentages of the corresponding components: a 58%, b 0.35%, c 1%, d 0.5%, e 26%, f 13.5%, and g 0.65%;
[0094] 2) The workpiece surface obtained in step 1) is cleaned with acetone, and then the workpiece surface is roughened with 46# white corundum (operated with a handheld air gun) until the workpiece surface roughness is Ra 4-6 and the sprayed surface is non-reflective;
[0095] 3) No spraying treatment is used.
[0096] Comparative Example 2
[0097] A grate bar for a roasting trolley, the preparation method of which comprises the following steps:
[0098] 1) Use chromium-nickel alloy static precision casting to form the grate bar base material (see the structural diagram Figure 1-4 ), the main chemical components used are based on the formula Fe a C b Si c Mn d Cr e Ni f M g The ingredients are prepared, wherein a, b, c, d, e, f, and g represent the atomic percentages of the corresponding components: a 58%, b 0.35%, c 1%, d 0.5%, e 26%, f 13.5%, and g 0.65%;
[0099] 2) The workpiece surface obtained in step 1) is cleaned with acetone, and then the workpiece surface is roughened with 46# white corundum (operated with a handheld air gun) until the workpiece surface roughness is Ra 4-6 and the sprayed surface is non-reflective;
[0100] 3) A CoNiCrAlY substrate layer is prepared on the surface of the workpiece obtained in step 2) by using a supersonic flame spraying process, and the main chemical components are selected according to the formula Co a Ni b Cr c Al d Y e The ingredients are prepared, wherein a is 52%, b is 25.5%, c is 12%, d is 10%, and e is 0.5%, and the average thickness of the prepared base layer is about 20 μm; the adopted supersonic flame spraying process parameters include spraying distance 350 mm, oxygen flow rate 1900 scfh, fuel flow rate 5.0 gph, auxiliary gas flow rate 25 scfh, and powder feeding speed 44 g / min;
[0101] 4) Use the main chemical components according to the formula Co a Cr b Al c Y d Ta eThe ingredients are prepared as follows: a 62%, b 23%, c 11%, d 0.5%, and e 3.5%. CoCrAlYTa powder and heat-resistant oxide powder Al2O3 are used as main raw materials, and a double powder feeding process is used for plasma spraying to prepare a CoCrAlYTa-based high-temperature resistant non-gradient surface layer, the average thickness of which is about 165μm; wherein the plasma spraying process parameters used include: a spray gun distance of 200mm, an argon flow rate of 52NLPM, a hydrogen flow rate of 13NLPM, and a current of 550A; the coating is sprayed 13 times at a powder feeding rate of 1.45-1.8g / min (Al2O3) and 27.5-28.5g / min (CoCrAlYTa) according to a 5wt% Al2O3 layer, and the first 7 times are sprayed with a coating thickness of 15μm per time, and the last 6 times are sprayed with a coating thickness of 10μm per time;
[0102] 5) The surface of the workpiece obtained in step 4) is sealed with a low-viscosity sealing resin, wherein the raw materials used in the low-viscosity sealing resin and their weight proportions are: 40% sodium silicate, 18% maleic anhydride polyester resin, 20% quartz powder, 5% bishydroxyphthalimide epoxy resin curing agent, 2% sodium hydroxide, and 15% calcium carbonate. The weighed raw materials are mixed evenly, then coated on the surface of the obtained CoCrAlYTa-based high-temperature resistant gradient surface layer, and heated to 230°C for rapid curing to obtain the grate bars for the baking trolley.
[0103] Comparative Example 3
[0104] A grate bar for a roasting trolley, the preparation method of which comprises the following steps:
[0105] 1) Use chromium-nickel alloy static precision casting to form the grate bar base material (see the structural diagram Figure 1-4 ), the main chemical components used are based on the formula Fe a C b Si c Mn d Cr e Ni f M g The ingredients are prepared, wherein a, b, c, d, e, f, and g represent the atomic percentages of the corresponding components: a 58%, b 0.35%, c 1%, d 0.5%, e 26%, f 13.5%, and g 0.65%;
[0106] 2) The workpiece surface obtained in step 1) is cleaned with acetone, and then the workpiece surface is roughened with 46# white corundum (operated with a handheld air gun) until the workpiece surface roughness is Ra4-6 and the sprayed surface is non-reflective;
[0107] 3) A CoNiCrAlY substrate layer is prepared on the surface of the workpiece obtained in step 2) by using a supersonic flame spraying process, and the main chemical components are selected according to the formula Co a Ni b Cr c Al d Y e The ingredients are prepared, wherein a is 52%, b is 25.5%, c is 12%, d is 10%, and e is 0.5%, and the average thickness of the prepared base layer is about 20 μm; the adopted supersonic flame spraying process parameters include spraying distance 350 mm, oxygen flow rate 1900 scfh, fuel flow rate 5.0 gph, auxiliary gas flow rate 25 scfh, and powder feeding speed 44 g / min;
[0108] 4) Use the main chemical components according to the formula Co a Cr b Al c Y d Ta e The ingredients are prepared as follows: a 62%, b 23%, c 11%, d 0.5%, and e 3.5%. CoCrAlYTa powder and heat-resistant oxide powder Al2O3 are used as the main raw materials, and a CoCrAlYTa-based high-temperature resistant gradient surface layer is prepared by plasma spraying using a double powder feeding process, and its average thickness is about 180 μm; wherein the plasma spraying process parameters used include: a spray gun distance of 200 mm, an argon flow rate of 52 NLPM, a hydrogen flow rate of 13 NLPM, and a current of 550 A; the first layer of the gradient coating, i.e., a 5wt% Al2O3 layer, adopts a powder feeding rate of 1.45-1.8 g / min (Al2O3), 27.5-28.5 g / min (CoCrAlYT a) Spraying 3 times, the average thickness of each spray coating is 10μm; the second layer of the gradient coating, i.e., the 10wt% Al2O3 layer, is sprayed 6 times at a powder feeding rate of 2.55-2.9g / min (Al2O3) and 22.5-26.5g / min (CoCrAlYTa), and the average thickness of each spray coating is 15μm; the third layer of the gradient coating, i.e., the 15wt% Al2O3 layer, is sprayed 4 times at a powder feeding rate of 3.5-4.5g / min (Al2O3) and 19.8-25.5g / min (CoCrAlYTa), and the average thickness of each spray coating is 15μm;
[0109] 5) An organic sealing agent is used on the surface of the workpiece obtained in step 4), comprising 55% acrylic emulsion and 45% dibutyl phthalate plasticizer.
[0110] Table 1 is a comparison table of the performance of the workpieces obtained in Examples 1 to 3 and Comparative Examples 1 to 3 after 20 cycles of simulated wear test:
[0111] Group Coating base layer μm Coating base top layer μm Wear thickness μm Example 1 20 180 99 Example 2 30 170 108 Example 3 35 165 135 Comparative Example 1 0 0 355 Comparative Example 2 20 165 196 Comparative Example 3 20 180 138
[0112] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the existing technology known to professional and technical personnel in this field.
Claims
1. A grate bar for a roasting trolley, characterized in that: It includes a chromium-nickel alloy substrate and a thermally sprayed composite coating deposited on the surface of the substrate after sealing treatment; the thermally sprayed composite coating includes a CoNiCrAlY base layer and a CoCrAlYTa-based high-temperature resistant gradient surface layer, wherein the CoCrAlYTa-based high-temperature resistant gradient surface layer includes CoCrAlYTa and heat-resistant oxides, and the content of the heat-resistant oxides is distributed in a gradient along the thickness direction of the coating.
2. The grate bar for the roasting trolley according to claim 1, characterized in that: In the CoCrAlYTa-based high-temperature resistant gradient surface layer, the content of the heat-resistant oxide is 3-20wt%, and the content of the heat-resistant oxide is distributed in a gradient decreasing manner from the surface to the inside along the thickness direction of the coating.
3. The grate bar for the roasting trolley according to claim 1, characterized in that: The stoichiometric formula of the CoCrAlYTa is shown in Formula I; Co a Cr b Al c Y d Dad e (I); Wherein, in terms of atomic percentage, 50%≤a≤65%, 15%≤b≤25%, 8%≤c≤12%, 0.3%≤d≤0.8%, and 0.5%≤e≤5%.
4. The grate bar for the roasting trolley according to claim 1, characterized in that: The heat-resistant oxide is one or more of aluminum oxide, chromium oxide, zirconium oxide, yttrium oxide, and lanthanum oxide.
5. The grate bar for the roasting trolley according to claim 1, characterized in that: The CoCrAlYTa-based high-temperature-resistant gradient surface layer is obtained by plasma spraying with CoCrAlYTa powder and heat-resistant oxide powder as main raw materials using a double powder feeding process.
6. The grate bar for the roasting trolley according to claim 1, characterized in that: The stoichiometric formula of the main components of the CoNiCrAlY substrate layer is shown in Formula II; Co a Ni b Cr c Al d Y e (II) Wherein, in terms of atomic percentage, 40%≤a≤60%, 20%≤b≤40%, 10%≤c≤20%, 5%≤d≤15%, and 0.1%≤e≤1%.
7. The grate bar for the roasting trolley according to claim 1, characterized in that: The CoNiCrAlY base layer is obtained by supersonic flame spraying using CoNiCrAlY powder as a main raw material.
8. The grate bar for the roasting trolley according to claim 1, characterized in that: The stoichiometric formula of the main components of the chromium-nickel alloy substrate is shown in formula (III); Feb a C b Si c Mr d Cr e Ni f M g (III); Wherein, M is a trace element and an unavoidable impurity element, and in terms of atomic percentage, 54%≤a≤65%, 0.2%≤b≤0.5%, 0%≤c≤2%, d≤2%, 24%≤e≤28%, and 11%≤f≤14%.
9. The grate bar for the roasting trolley according to claim 1, characterized in that: The sealing agent used in the sealing treatment is a low-viscosity liquid resin; the components and their mass percentages include: 30% to 50% sodium silicate, 10% to 25% polyester resin, 10% to 30% quartz powder, 2% to 10% curing agent, 0.5% to 3% sodium hydroxide, and 5% to 15% calcium carbonate.
10. The method for preparing the grate bars for the roasting trolley according to any one of claims 1 to 9, characterized in that: The steps include: 1) The chromium-nickel alloy is precision-casted into grate bars according to the designed structure, and the cast grate bars are cleaned and roughened; 2) preparing a CoNiCrAlY substrate layer on the surface of the workpiece obtained in step 1) by using a supersonic flame spraying process; 3) using a plasma thermal spraying process to prepare a CoCrAlYTa-based high temperature resistant gradient surface layer on the surface of the workpiece obtained in step 2); 4) A sealing agent is coated on the surface of the workpiece obtained in step 3), and heated and cured to obtain the grate bars for the baking trolley.
Citation Information
Patent Citations
Thermal-spraying hole sealing agent with high temperature stability and application method thereof
CN104804615A
Method for preparing NiCrBSi-TiN gradient composite coating abrasion-resistant belt on the surface of drill rod joint
CN107267908A
Continuous annealing furnace high-temperature furnace roller ZrB2 modified CoCrAlTaY-Y2O3 protective coating and preparation method thereof
CN110643926A
Alloy material with multielement gradient composite coating deposited on surface and preparation method of alloy material
CN111996495A
Plasma spraying ceramic powder, ceramic composite coating and preparation method thereof
CN119118634A